Household food insecurity and nutritional status of pre-school children following relaxation of corona virus disease-2019 (COVID-19) restrictions - Abdullah H., Anaqreh (2025)
Background & aimsStudies found a high prevalence of household food insecurity (HFI) and malnutrition and an association between them during the movement restriction period of the corona virus disease-2019 (COVID-19) pandemic. This nutritional status should have improved by now as movement restrictions, including quarantine, have been lifted. Therefore, the goal of this cross-sectional study was to determine the current prevalence of HFI and malnutrition and their associations and contributing factors among pre-school children (i.e., children under the age of 5 years) following relaxation of the COVID-19 restrictions in Jordan. MethodsA sample of 386 children (197 boys and 189 girls) in Irbid, Jordan, were recruited in this study following the simple random sampling method. The levels of HFI and malnutrition were assessed using the Food Insecurity Experience Scale (FIES) and the World Health Organization (WHO) growth reference values, respectively. Relevant information were managed and measurements made and employed to calculate four major anthropometric indicators for the sample children (weight for height (WHZ), height for age z-score (HAZ), weight for age z-score (WAZ) and body mass index (BMI)-for-age z-score. ResultsThe results of analysis pointed out that prevalence of food security among the sample children was 58.2 %, where 19.9 % of the kids were experiencing moderate food insecurity and 38.3 % were suffering from severe food insecurity. On the other hand, prevalence of malnutrition among those children was 1.81 %, where 1.55 % of the kids were emaciated and 1.26 % were severely emaciated. The results also indicated that mother's age, number of children in the family, income of the family, monthly expenses on food and beverages and the energy expenses contributed significantly (p < 0.05) to food insecurity. Moreover, the study found that HFI had negative correlations with WHZ (r = −0.272, p = 0.000), WAZ (r = −0.193, p = 0.000) and BMI-for-age z-score (r = −0.263, p = 0.000) and a positive correlation with HAZ (r = 0.041, p = 0.00). ConclusionsThe study reports high prevalence of HFI among children under the age of 5 years in Jordan, even after relaxation of the COVID-19 restrictions on mobility. However, prevalence of malnutrition among this group of the population is low. These results spotlight the continued impact of the COVID-19 crisis on the financial statuses of households.